Role of Interleukin-28B in clearance of HCV in acute and chronic hepatitis patients in Kirkuk city - Abdullah Alazzawy, Muhannad (Kurdistan Journal of Applied Research, 2018)
A cross sectional study was conducted in Kirkuk city from June 2017 to March 2018. The number of hepatitis patient understudy were 62 hepatitis C (27 acute and 35 chronic) whose ages were between 20-75 years old. The purpose of this study was to evaluate the effect of IL28B in the clearance of HCV. These patients admitted to Hepatology and Gastroenterology centers of Kirkuk. The control group who were matched to the patients studied, included 30 individuals who admitted to blood bank for blood donation, for molecular test of HCV Real-time quantitative test and serum IL-28B ELISA. The study exhibited that 81.48 % of acute HCV patient who positive by ELISA were positive by PCR and 82.86 % of chronic HCV patients were positive by PCR with highly significant relation between them. Regarding the relation of IL-28B with HCV infection, the study presented that the highest mean of IL-28B was recorded among PCR –ve acute HCV patients (17.78 pg/ml) followed by PCR +ve acute HCV and the lowest means was found in the control group with highly significant differences among the groups. The study indicated that the highest mean of IL-28B was recorded among PCR –ve chronic HCV patients (17.78 pg/ml) followed by PCR +ve chronic HCV and the lowest means was found in the control group with highly significant relation. The study showed that the highest mean of ALT and AST were found in acute HCV patients (72.06 and 36.73 IU/ml) respectively followed by chronic HCV and the control group with highly significant relation among the groups.